A hydrophobic three-dimensionally networked boron-doped diamond electrode towards electrochemical oxidation. Issue 51 (6th June 2016) - He, Yapeng; Lin, Haibo; Wang, Xue; Huang, Weimin; Chen, Rongling; Li, Hongdong
Abstract : Three-dimensionally networked boron-doped diamond with a microstructure and enhanced mass transfer showed excellent electro-oxidation ability towards contaminants. Abstract : A boron-doped diamond electrode with a three-dimensional network was fabricated on a mesh titanium substrate. Properties such as higher surface area, enhanced mass transfer and a hydrophobic surface endowed the prepared electrode with excellent electrochemical oxidation ability towards contaminants.